Controlling malaria and African trypanosomiasis: The role of the mouse - Foote, S.J.; Iraqi, F.A.; Kemp, Stephen J. (Oxford University Press, 2005)
Malaria and trypanosomiasis are vector-borne protozoal diseases which disproportionately affect the poor. Both give rise to immense human suffering; malaria exerts its effect directly on human health, while trypanosomiasis causes damage largely though its effect on the health and productivity of the livestock on which so many poor people depend. These diseases both have multifaceted and poorly understood mechanisms of pathogenesis, combined with relatively complex life cycles characterised by multiple stages in both insect vector and mammalian host. In both cases, there is a dramatic effect of host genotype on disease progression. This effect is apparent in both the human and cattle hosts and among inbred mouse strains. This provides an opportunity to use the mouse to probe the mechanisms underlying resistance or susceptibility to pathology. The availability of high-density linkage maps, the genome sequence and transcriptomics tools has transformed the power of the mouse to illuminate such fundamental aspects of the host-parasite interaction.